Root perforations: a review of diagnosis, prognosis and materials - Carlos Estrela; Daniel de Almeida Decurcio; Giampiero Rossi-Fedele; Julio Almeida Silva; Orlando Aguirre Guedes; Álvaro Henrique Borges (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract: Root perforation results in the communication between root canal walls and periodontal space (external tooth surface). It is commonly caused by an operative procedural accident or pathological alteration (such as extensive dental caries, and external or internal inflammatory root resorption). Different factors may predispose to this communication, such as the presence of pulp stones, calcification, resorptions, tooth malposition (unusual inclination in the arch, tipping or rotation), an extra-coronal restoration or intracanal posts. The diagnosis of dental pulp and/or periapical tissue previous to root perforation is an important predictor of prognosis (including such issues as clinically healthy pulp, inflamed or infected pulp, primary or secondary infection, and presence or absence of intracanal post). Clinical and imaging exams are necessary to identify root perforation. Cone-beam computed tomography constitutes an important resource for the diagnosis and prognosis of this clinical condition. Clinical factors influencing the prognosis and healing of root perforations include its treatment timeline, extent and location. A small root perforation, sealed immediately and apical to the crest bone and epithelial attachment, presents with a better prognosis. The three most widely recommended materials to seal root perforations have been calcium hydroxide, mineral trioxide aggregate and calcium silicate cements. This review aimed to discuss contemporary therapeutic alternatives to treat root canal perforations. Accordingly, the essential aspects for repairing this deleterious tissue injury will be addressed, including its diagnosis, prognosis, and a discussion about the materials actually suggested to seal root canal perforation.